Ultra Thin Flexible Octagonal Metamaterials Absorber - H. Hassan; M. Abu (Institute of Advanced Engineering and Science, 2018)
An ultra thin flexible octagonal metamaterial absorber on 0.13 mm fastFilm D27 material has been presented in this paper. CST microwave studio was used in designing and simulating the octagonal metamaterial absorber. The flexible octagonal metamaterial absorber was resonated at 10 GHz with highly perfect absorbance of 99.98%. However, Full Width Half Maximum (FWHM) of the absorbance was relatively small 135 MHz affected from the ultra thin substrate used. By using triangular lattice arrangement of the unit cell, the FWHM could be increased to 171 MHz. Besides that, combination of resonating frequencies technique also had increased the FWHM more than 74% increment from basic unit cell with one resonance frequency. The flexibleness of the metamaterial absorber could increase the functionality of the metamaterial absorber to be used in any application especially in reducing radar cross section for stealth application.